(untitled) (Research, Society and Development, 2023)
Introduction: Schizophrenia is a chronic and serious psychiatric illness, in addition to being extremely debilitating and which carries with it a very large stigma for its carriers. It is one of the diseases that causes the most disability and therefore the patient needs comprehensive care, aiming not only at resolving the psychiatric condition, but also at improving well-being and reducing suffering. Objective: This work aims to review the literature on palliative care in patients with schizophrenia and identify the applicability and importance of such a practice. Method: narrative literature review, using the databases: Scientific Electronic Library Online (ScieELO), UpToDate and Medical Literature Analysis and Retrieval System Online (MEDLINE). Using the following keywords: “Palliative Care”, “Schizophrenia” and “Mental Health”. Inclusion and exclusion criteria were applied and a total of 61 articles were used. Results and Discussion: Schizophrenia is a serious chronic mental illness that results in marginalization and stigma for patients. Approximately four to seven million people worldwide suffer from severe treatment-resistant schizophrenia. These patients may have a high level of negative symptoms, leading to impaired quality of life and social functioning. The range of palliative care approaches in medicine is very wide, from targeted short-term measures for the relief of distressing symptoms to palliative sedation. Palliative care services for people with schizophrenia must adopt an inclusive approach. Conclusion: Palliative care can offer comfort to patients with schizophrenia and their families, especially to marginalized people.